Residency-Affiliated Academic Neurosurgeons (RAAN): A Cross-Sectional Analysis of Neurosurgery Residency Program Rankings - Ciaran Powers; Sheeny Vo; Olivia Duru (International Journal of Medical Students)
Background: Existing neurosurgery residency rankings do not assess programs based on graduate placement in academic faculty positions. We sought to develop a novel ranking system of neurosurgery programs to identify programs that produced academic faculty and evaluated these programs relative to established ranking systems. This novel ranking system, the Residency Affiliated Academic Neurosurgeons, was compared to the Doximity Residency Navigator, and Blue Ridge Institute for Medical Research.